Actin Dynamics as a Multiscale Integrator of Cellular Guidance Cues - Bull, Abby L.; Campanello, Leonard; Hourwitz, Matt J.; Yang, Qixin; Zhao, Min; Fourkas, John T.; Losert, Wolfgang (Frontiers in Cell and Developmental Biology, 2022)
Migrating cells must integrate multiple, competing external cues that guide cell migration. However, it is not well understood how cells prioritize among these cues. We investigate external cue integration by monitoring the response of wave-like, actin-polymerization dynamics, the driver of cell motility, to combinations of nanotopographies and electric fields in neutrophil-like cells. The electric fields provide a global guidance cue and approximate conditions at wound sites in vivo. The nanotopographies have dimensions like those of collagen fibers, and act as a local esotactic guidance cue. We find that cells prioritize guidance cues with electric fields dominating long-term motility by introducing a unidirectional bias in the locations of wave nucleation sites that competes successfully with the wave guidance provided by the bidirectional nanotopographies.